Double Helix Twisted and Coiled Soft Actuator from Spandex and Nylon. Issue 11 (31st August 2018) - Kim, Kihyeon; Cho, Kyeong Ho; Jung, Ho Sang; Yang, Sang Yul; Kim, Youngeun; Park, Jae Hyeong; Jang, Hoyoung; Nam, Jae‐Do; Koo, Ja Choon; Moon, Hyungpil; Suk, Ji Won; Rodrigue, Hugo; et al.
Abstract : This paper introduces a fabrication method and properties of newly developed Twisted and Coiled soft Actuator (TCA) from nylon and spandex. The TCA, a thermally driven actuator, is one of the promising soft actuators that shows considerable strain compared to the others. Typically, TCA is fabricated from single polymer fiber such as the spandex and nylon. However, TCA from each material shows some limits. The spandex TCA (STCA) shows siginificant strain more than 45%. However, since the spandex is non‐conductive material, the STCA requires additional heat source such as heat gun. On the other hand, since the nylon TCA (NTCA) is fabricated from silver‐coated nylon, it is capable of Joule heating. However, the strain is considerably smaller than that of the STCA. Newly developed TCA, Double helix TCA (DTCA), is composed of both of them. As a result, the DTCA inherits the properties of the STCA and the NTCA. It is capable of Joule heating showing high strain over 40%. Since, DTCA is very soft, light, and cheap, it has various applications in the field of robots including artificial limbs. Abstract : An artificial muscle fabricated from nylon and spandex is introduced. As the spandex is ultra‐stretchable, it is very soft and shows significantly large strain compared to the other soft actuators. Since the nylon is coated by silver, it is capable of Joule heating. It results in compact system without any other heat source such as heat gun.